2014
DOI: 10.1016/j.jmacro.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Are public preferences reflected in monetary policy reaction functions?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Several studies have empirically demonstrated that inflation aversion plays an essential role in the formulation of monetary policy. Hayo (1998) and Neuenkirch (2014), for example, show that the levels of inflation and interest rates set by central banks systematically vary according to countries' average levels of inflation aversion. Further, other studies suggest that in addition to inflation aversion's effect on macroeconomic outcomes, it also affects a country's “choice of monetary institutions” and “the extent of [its] international monetary cooperation” (Scheve, 2004, p. 1) 5 .…”
Section: Theorymentioning
confidence: 99%
“…Several studies have empirically demonstrated that inflation aversion plays an essential role in the formulation of monetary policy. Hayo (1998) and Neuenkirch (2014), for example, show that the levels of inflation and interest rates set by central banks systematically vary according to countries' average levels of inflation aversion. Further, other studies suggest that in addition to inflation aversion's effect on macroeconomic outcomes, it also affects a country's “choice of monetary institutions” and “the extent of [its] international monetary cooperation” (Scheve, 2004, p. 1) 5 .…”
Section: Theorymentioning
confidence: 99%